A Physicochemical and Pharmacological Study of the Newly Synthesized Complex of Albendazole and the Polysaccharide Arabinogalactan from Larch Wood - S. Chistyachenko, Yulia; S. Meteleva, Elizaveta; Y. Pakharukova, Maria; V. Katokhin, Aleksey; V. Khvostov, Mikhail; I. Varlamova, Anastasiya; I. Glamazdin, Igor; S. Khalikov, Salavat; E. Polyakov, Nikolay; A. Arkhipov, Ivan; G. Tolstikova, Tatyana; A. Mordvinov, Viatcheslav; et al. (Current Drug Delivery, 2015)
Inclusion complexes of albendazole (ABZ) with the polysaccharide arabinogalactan from larch wood Larix sibirica and Larix gmelinii were synthesized using a solid-state mechanochemical technology. We investigated physicochemical properties of the synthesized complexes in the solid state and in aqueous solutions as well as their anthelmintic activity against Trichinella spiralis, Hymenolepis nаna, Fasciola hepatica, Opisthorchis felineus, and mixed nematodoses of sheep. Formation of the complexes was demonstrated by means of intrinsic solubility and the NMR relaxation method. The mechanochemically synthesized complexes were more stable in comparison with the complex produced by mixing solutions of the components. The complexes of ABZ showed anthelmintic activity at 10-fold lower doses than did free ABZ. The complexes also showed lower acute toxicity and hepatotoxicity. These results suggest that it is possible to design new drugs on the basis of the ABZ:arabinogalactan complex that are safer and more effective than albendazole.
Keywords: mechanical activation